Transformation of galena to pyromorphite produces bioavailable sulfur for neutrophilic chemoautotrophy. Issue 6 (14th July 2016) - Walczak, A. B.; Kafantaris, F.‐C. A.; Druschel, G. K.; Yee, N.; Young, L. Y.
Abstract: The aqueous concentration of lead [Pb(II)] in geochemical environments is controlled by the solubility of Pb‐bearing minerals and their weathering products. In contaminated soils, a common method for in situ stabilization of Pb(II) is the addition of phosphate to convert more redox sensitive sulfide minerals into sparingly soluble pyromorphite [Pb5 (PO4 )3 X]. In this study, we conducted experimental studies to investigate the fate of reduced sulfur during the conversion of galena [PbS] to chloropyromorphite [Pb5 (PO4 )3 Cl]. Powder X‐ray diffraction analysis indicated that the reaction of phosphate with galena under oxic conditions resulted in the oxidation of sulfide and formation of elemental sulfur [S8 ]. Under oxic abiotic conditions, the S8 was retained in the solid phase, and negligible concentrations of sulfur as sulfide and thiosulfate were detected in the aqueous phase and only a small amount of sulfate. When PbS reacted in the presence of the chemoautotrophic organism Bosea sp. WAO, the S8 in the secondary mineral was oxidized to sulfate. Strain WAO produced significantly more sulfate from the secondary S8 than from the primary galena. Microscopic analysis of mineral–microbe aggregates on mineral‐embedded slide cultures showed that the organism was colocalized and increased in biomass over time on the secondary mineral surface supporting a microbial role. The results of this study indicate that stimulation of sulfur‐oxidizing activity may be a direct consequence of phosphate amendments to Pb(II)‐contaminated soils.